Metabolic changes of glycerophospholipids during the reparative phase after myocardial infarction injury - Wang, Jin; Yu, Xinyi; Wang, Tingyu; Cai, Wenbin; Hua, Tong; Duan, Jinjie; Zhang, Xu; Zhu, Yi; Yao, Liu (Frontiers in Cardiovascular Medicine, 2023)
Introduction Myocardial infarction (MI) is a fatal manifestation of coronary heart disease, and its underlying mechanism is still largely unknown. Lipid levels and composition alterations predict the risk of MI complications. Glycerophospholipids (GPLs) are important bioactive lipids and play a crucial role in the development of cardiovascular diseases. However, the metabolic changes in the GPLs profile during post-MI injury remain unknown. Methods In the current study, we constructed a classic MI model by ligating the left anterior descending branch and assessed the alterations in both plasma and myocardial GPLs profiles during the reparative phase post-MI by liquid chromatography–tandem mass spectrometry analysis. Results We found that myocardial GPLs, but not plasma GPLs, were markedly changed after MI injury. Importantly, MI injury is associated with decreased phosphatidylserine (PS) levels. Consistently, the expression of phosphatidylserine synthase 1 (PSS1), which catalyzes the formation of PS from its substrate phosphatidylcholine, was significantly reduced in heart tissues after MI injury. Furthermore, oxygen-glucose deprivation (OGD) inhibited PSS1 expression and reduced PS levels in primary neonatal rat cardiomyocytes, while overexpression of PSS1 restored the inhibition of PSS1 and the reduction in PS levels caused by OGD. Moreover, overexpression of PSS1 abrogated, whereas knockdown of PSS1 aggravated, OGD-induced cardiomyocyte apoptosis. Conclusions Our findings revealed that GPLs metabolism was involved in the reparative phase post-MI, and cardiac decreased PS levels, resulting from inhibition of PSS1, are important contributor to the reparative phase post-MI. PSS1 overexpression represents a promising therapeutic strategy to attenuate MI injury.